Screening For Small Molecule Inhibitors Of p27Kip1 Degradation - Ooi, Li Ching (2012)
In a majority of human cancers, the cyclin-dependent kinase (CDK) inhibitor p27Kip1 is commonly found to be deregulated due to proteolysis by the ubiquitin-proteasome pathway involving the SCFSkp2 E3 ligase. Although proteasome inhibitors act to stabilize p27Kip1, small molecules agents inhibiting the degradation of p27Kip1 by the function of SCFSkp2 E3 ligase may contribute to the development of a specific targeted drug that could prove to be more efficacious with less side effects. In this work, we have developed a high-throughput screening system based on phosphorylation dependent protein-protein interaction using the baculovirus protein expression system.